2019
DOI: 10.1002/ese3.551
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic modeling of layered rocks incorporating planes of weakness and volumetric stress

Abstract: Layered rocks exhibit notable transverse isotropy and have a significant impact on the deformation and failure characteristics of underground structures. To a large extent, the mechanical properties of layered rocks are related to the structure and stress state of their bedding planes. To obtain an in‐depth understanding of the deformation and yield characteristics of layered rocks, a mechanical model for layered rocks incorporating planes of weakness and volumetric stress is proposed by improving the strain‐h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 44 publications
0
29
0
Order By: Relevance
“…The study area is located in the SW Taiwan Basin of the northeastern South China Sea, where submarine faults, bottom channels, and mud diapirs were developed [32]. Many studies have analyzed the hydraulic properties of rock fractures [33][34][35][36][37][38][39][40] and suggested that these fracture systems in strata are favorable pathway for fluid migration [41][42][43][44][45], but the fracture systems develop heterogeneously in natural environments, and the fracture prediction is quite difficult and needs more experimental investigations [46][47][48][49].…”
Section: Methodsmentioning
confidence: 99%
“…The study area is located in the SW Taiwan Basin of the northeastern South China Sea, where submarine faults, bottom channels, and mud diapirs were developed [32]. Many studies have analyzed the hydraulic properties of rock fractures [33][34][35][36][37][38][39][40] and suggested that these fracture systems in strata are favorable pathway for fluid migration [41][42][43][44][45], but the fracture systems develop heterogeneously in natural environments, and the fracture prediction is quite difficult and needs more experimental investigations [46][47][48][49].…”
Section: Methodsmentioning
confidence: 99%
“…erefore, it is necessary to determine the geometric characteristics of cantilever beam structure, including its thickness, breaking length, and position on the coal wall. According to the geological conditions of 8211 working face, the thickness of cantilever beam is 13.5 m, and the breaking length can be solved by the following formula [42]:…”
Section: Geometric Characteristics Of Cantilever Beam Structurementioning
confidence: 99%
“…Its height is an intuitive description of the shape of the water-flowing fracture zone. At present, field observation is the most accurate method to determine the DHOWFFZ, and the commonly used observation methods include underground double-end water plugging observation method, surface drilling flushing fluid consumption observation method, high-density resistivity method, and television imaging method [7][8][9]. However, the traditional empirical formula method is generally adopted in the prediction of DHOWFFZ currently in China because the complex field observation operation may affect the efficient production in coal mines.…”
Section: Introductionmentioning
confidence: 99%